Role of stem cell derivatives in inflammatory diseases - Yang, Yuxi; Peng, Yiqiu; Li, Yingying; Shi, Tingjuan; Luan, Yingyi; Yin, Chenghong (Frontiers in Immunology, 2023)
Mesenchymal stem cells (MSCs) are pluripotent stem cells with the capacity for self-renewal and multidirectional differentiation into osteoblasts, chondrocytes, adipocytes, and other types of cells. Stem cell derivatives are spherical vesicles secreted by MSCs that contain many anti-inflammatory compounds and modulate the immune and inflammatory response by interacting with immune effector cells. These cells exhibit stem cell properties, strong potential for self-renewal, and show multi-lineage differentiation, and they have therefore been widely employed in stem cell therapy, tissue regeneration, as well as inflammatory diseases. Numerous studies have shown that most diseases are closely associated with inflammation, which is extremely destructive, can lead to necrosis of organ parenchymal cells and deposit excessive extracellular matrix in the tissues. Stem cell derivatives are capable of reproducing MSC function and overcoming the limitations of traditional cell therapy. Therefore, using stem cell derivatives instead of MSCs to treat inflammatory diseases appears to be a promising cell-free treatment strategy. In this review, we highlight the current understanding of MSCs-derived exosomes and discusses the regulatory role of MSCs-derived exosomes in inflammatory diseases and their potential application in clinical diagnosis and treatment.